An analysis of the scale processes in Supermarkets attended by the ALI program at Seridó Region - Silva, Rauane Dharlly; Silva, Napiê Galvê Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The culture of innovation is intervening for the development of sustainable competitiveness between companies factor. This study aims to analyze the degree of innovation in Supermarkets served by the Local Innovation Agents program (ALI), in the Eastern Seridó. The analysis is performed with a special focus on the dimension processes. Thus, use is made of research, quantitative indicators generated from the Innovation Radar and qualitative through observations conducted onsite visits by monitoring the ALI program. Using the information obtained, it is seen that the degree of innovation should be working in companies, with the aim of improving the activities in your internal environment, both for control and for growth. Thus, it appears that innovation is rather competitive differentiation criterion, that both can, as should be implemented in the environment of Micro and Small Enterprises.